2011
DOI: 10.1007/s00167-011-1652-4
|View full text |Cite
|
Sign up to set email alerts
|

Fracture at the stem–condylar junction of a modular femoral prosthesis in a varus–valgus constrained total knee arthroplasty

Abstract: Case report, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Based on the evidence in both cases, failure at the modular junction was attributed to aseptic loosening of the femoral component distally in combination with a weakening of osseous support, as suggested by the apparent bone loss under the implants visible from patient radiographs. Similarly, Nikolopoulos et al reported a single case of modular junction failure in a cemented stemmed revision prosthesis attributed to loss of fixation through poor cementing of the prosthesis and a lack of cancellous bone support at the time of revision implantation. This numerical study strongly supports the assertion that lack of osseous support leads to high junction stresses, a loss of metaphyseal fix was also found to increase stresses at the modular junctions, though not to the same extent as a lack of osseous support.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Based on the evidence in both cases, failure at the modular junction was attributed to aseptic loosening of the femoral component distally in combination with a weakening of osseous support, as suggested by the apparent bone loss under the implants visible from patient radiographs. Similarly, Nikolopoulos et al reported a single case of modular junction failure in a cemented stemmed revision prosthesis attributed to loss of fixation through poor cementing of the prosthesis and a lack of cancellous bone support at the time of revision implantation. This numerical study strongly supports the assertion that lack of osseous support leads to high junction stresses, a loss of metaphyseal fix was also found to increase stresses at the modular junctions, though not to the same extent as a lack of osseous support.…”
Section: Discussionmentioning
confidence: 98%
“…Previous clinical case studies have indicated that a lack of osseous support, in combination with loss of metaphyseal fixation, might be a key factor in the failure of modular components . In a recent retrieval study, Issack et al reported two cases of failure at the modular taper lock of constrained condylar prostheses with large diameter stems and distal femoral augments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations